Human papillomavirus–associated oropharyngeal cancer among patients aged 70 and older: Dramatically increased prevalence and clinical implications. (November 2018) - Lu, Diana J.; Luu, Michael; Mita, Alain; Scher, Kevin; Shiao, Stephen L.; Yoshida, Emi P.; Sittig, Mark P.; Mallen-St Clair, Jon; Ho, Allen S.; Zumsteg, Zachary S.
Abstract: Background: Oropharyngeal squamous cell carcinoma (OPSCC) is increasing in incidence among older adults. However, the role of human papillomavirus (HPV) in driving this trend and its prognostic significance in this population have not been established. Methods: The National Cancer Database was queried for patients with OPSCC diagnosed from 2010 to 2015 undergoing either surgery or radiotherapy (RT) with known HPV status. Older adults were defined as those aged 70 years or older. Results: Among 43, 427 OPSCC patients, the proportion of HPV-positive OPSCC increased from 45.1% to 63.3% in older adults (P < 0.001). In 19, 358 patients meeting the inclusion criteria for survival analyses, HPV positivity was associated with improved survival for older adults undergoing either definitive RT (hazard ratio [HR] = 0.63, 95% confidence interval [CI] 0.55–0.72, P < 0.001) or surgery (HR = 0.37, 95% CI 0.25–0.53, P < 0.001) in multivariable analysis. In propensity score–matched cohorts, 3-year overall survival was 69.1% versus 55.5% (P < 0.001) in older adults with HPV-positive and HPV-negative OPSCC undergoing definitive RT, respectively, and 88.5% versus 69.1% (P = 0.001) for older adults undergoing surgery. Although HPV positivity was associated with improved survival among all age groups receiving RT, the magnitude of the effect diminished with increasing age (interaction P < 0.001). No interaction between age and the impact of HPV status on survival was seen for surgical patients (interaction P = 0.72). Conclusions: The epidemiologic landscape of HPV-positive OPSCC is evolving, with a dramatic increase in the proportion of HPV-associated OPSCC among patients 70 years or older. HPV remains a powerful predictor of improved survival in elderly patients, but with less pronounced effect on older adults undergoing definitive RT. Highlights: The prevalence of human papillomavirus (HPV)–positive oropharyngeal cancers is increasing in adults aged 70 years and older. HPV positivity conveys dramatically improved survival in the older adult population. The impact of HPV decreases with increasing age for patients getting exposed to radiation. HPV conveys a constant survival benefit independent of age for surgery patients.